2017
DOI: 10.1021/acs.jproteome.5b01052
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification and Analysis of Arginine-Methylated Proteins of Plasmodium falciparum at Asexual Blood Stages

Abstract: Plasmodium falciparum undergoes a tightly regulated developmental process in human erythrocytes, and recent studies suggest an important regulatory role of post-translational modifications (PTMs). As compared with Plasmodium phosphoproteome, little is known about other PTMs in the parasite. In the present study, we performed a global analysis of asexual blood stages of Plasmodium falciparum to identify arginine-methylated proteins. Using two different methyl arginine-specific antibodies, we immunoprecipitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…GFP-Trap ® _A beads were allowed to bind to parasite lysate by tumbling the tube end-over-end. Proteins were eluted in 50 μl elution buffer, digested with trypsin and peptides were analysed by mass spectrometry 41 .…”
Section: Methodsmentioning
confidence: 99%
“…GFP-Trap ® _A beads were allowed to bind to parasite lysate by tumbling the tube end-over-end. Proteins were eluted in 50 μl elution buffer, digested with trypsin and peptides were analysed by mass spectrometry 41 .…”
Section: Methodsmentioning
confidence: 99%
“…This includes Ellagic Acid, which was previously indicated as potent against asexual parasites (37). Although antioxidant pleiotropic effects of this compound cannot be ignored, the multistage activity reported here suggests a possible role of arginine methylation during these stages (38), but not in mature gametocytes.…”
Section: Discussionmentioning
confidence: 71%
“…The in silico molecular modeling and structural analysis revealed that PfU52 displayed structural similarities with its human homolog and it also exhibits some distinctive properties that can be used for drug design [65]. It has been reported in recent studies that PfU52 is methylated at arginine and lysine residues and this modification may regulate its activities [48,49].…”
Section: Dead-box Helicases Of Plasmodium Falciparummentioning
confidence: 98%
“…The ATPase and DNA helicase activities of PfH45 were effectively inhibited by nogalamycin, actinomycin, daunorubicin, netropsin, ethidium bromide, and DAPI . Previous studies have reported that PfH45 is phosphorylated by protein kinase C and recent studies have shown that it is methylated at arginine residues suggesting that post‐translational modifications may regulate its activities . It will be interesting to study the effect of hippuristanol on the activity of PfH45.…”
Section: Dead‐box Helicases Of Plasmodium Falciparummentioning
confidence: 99%